P115 Chronic Diesel Exhaust Particle (DEP) exposure differentially alters monocyte differentiation and function in healthy controls compared to COPD. (2nd December 2011) - Chaudhuri, N; Jary, H; Lea, S; Khan, N; Parker, L C; Singh, D; Sabroe, I
Abstract : Introduction and Objectives: Alveolar macrophages are heavily implicated in the pathogenesis COPD. During chronic inflammation, macrophages mature continuously from infiltrating monocytes that are continually recruited to the airways. We have previously found DEP modulate life span and function of monocytes from healthy donors, but their effects on monocytes of people with COPD are unknown, and were therefore the subject of this study. Methods: Monocytes were purified from the blood of patients with GOLD II/III COPD and healthy age matched controls Monocyte-derived macrophages (MDMs) were generated in the presence or absence of DEP and their lifespan studied. Cytokine generation in response to TLR agonists and heat killed bacteria was assessed by ELISA and expression of CD14 was measured by FACS. Results: Chronic exposure of monocytes from patients with COPD to DEP concentrations above 10 μg/ml caused a significant reduction in cell survival. Lower concentration of chronic DEP exposure, as low as 1 μg/ml, caused impairment of cytokine responses to LPS and heat killed Escherichia Coli, and this phenotype was associated with a reduction in CD14 surface marker expression. However, COPD monocytes were generally more resistant to the effects of DEP compared to healthy control cells. Conclusions: In this study monocytes from healthy volunteers appeared to be more susceptible to the harmful effects of chronic DEP exposure compared to those from individuals with COPD. These findings reinforce the evidence that circulating leukocytes in COPD patients have altered phenotypes.